THE INFLUENCE OF WORK DISCIPLINE, OCCUPATIONAL SAFETY AND HEALTH, AND POSITION PROMOTION ON EMPLOYEE PERFORMANCE AT PT. ASTRA INTERNATIONAL DAIHATSU, TBK MEDAN - Santi Devi Silalahi; Dherma Yusnita; Khomeiny Yunior; Hendra Saputra (Mount Hope Economic Global Journal, 2024)
In this modern era, the success of companies in business competition and adapting to rapid business changes has become very dependent on the superior performance of employees. In a global market full of competition, every employee is expected to provide their best performance. Employees' ability to adapt to changes in technology, organizational structure, and business environment has been the key to company growth. The aim of this study is to identify the factors that Work Discipline, Occupational Safety and Health, and Position Promotion have an influence on employee performance at PT. Astra International Daihatsu, Tbk Medan. Employees who are highly disciplined tend to contribute consistently and this can influence their overall performance. Safe and healthy working situations and conditions can also improve employee performance, because they can focus on their tasks without worrying about the risk of work-related injuries or illnesses. The hope of getting a promotion can also motivate employees to work harder, improve the quality of their performance, and influence productivity levels. These three factors provide valuable insights for companies in developing more productive human resource policies. Researchers used quantitative methods in this research with a sample of 109 respondents. This research found that employees at the company PT. Astra International Daihatsu, Tbk Medan will produce good performance if the work discipline and position promotion factors are also good. Specifically, this performance is influenced by discipline and promotion factors, but is not influenced by occupational safety and health factors of PT employees. Astra International Daihatsu, Tbk Medan.